Diary of A Restless Teacher: How We Can Shift to The Learner-Centered Approach (European Journal of Teaching and Education, 2020)
Beyond doubt, learner-centered approach has proved to be effective for better learning outcomes. Drawing on a personal experience, I present in this paper how a mix of being involved with a series of training workshops, discussion with my colleagues, and the ‘accidental’ introduction of social constructivist tools in my classrooms gradually changed my view on the potential of technology in the learning process. It also looks at how a reflective diary helped me to leverage these experiences more effectively. It records a journey of interaction with education designers, other teachers and students, and how I selected the resources and approaches that might produce better learning opportunities for the learners. It further looks at the adoption of learning technology as a vehicle for developing the teacher’s own understanding of the power of social learning. I address some of the challenges I encountered while making the shift. The paper concludes that intentionally reviewing one’s teaching in collaboration with education experts, one’s colleagues and learners is a positive experience and has resulted in an approach that has considerably shifted the focus to learners. I am optimistic that my fellow teachers find my experiences inspiring and we collectively can bring about a change for the benefit of the education sector.